Strategy Formulation for KJPP Irfan dan Rekan (The Indonesian Journal of Business Administration, 2015)
Abstract.KJPP Irfan dan Rekan is a appraisal firm that provide appraisal service based on current code of conduct and regulation/policy, already has a certificate issued and endorsed by Appraisal Association (MAPPI) and registered by Finance Ministry. established on October 30, 2013. Previously this company named KJPP Irfan established in 2009. Problem Question in this Final Project is How KJPP Irfan and rekan keep competitive and sustain in this industry and to optimize profit from existing customer and get a new customer. This final project will identify External Analysis and Internal Analysis. External analysis will elaborate in PEST analysis and Porter’s Five Forces. Internal Analysis will elaborate in Value Chain Analysis and existing Business Model Canvas. Then, summarizing SWOT. strategic formulation tools are using directional strategy using IE Matrix dan QSPM, portfolio strategy using GE matrix and new business model canvas. alternatif strategy that company could choose, in term of limited of human resources are horizontal integration, market penetration, and market development. QSPM indicates company should do market development. Portfolio strategy using GE Matrix find that Fixed Asset Valuation into protect position. Feasibility Study and Project Monitoring into selectively/manage for earnings. Parenting strategy that company do is budgetary control. One of important factor of business model canvas is a key resources, company should build trust, because it could support company to get a new customer and retain existing customer. Conclusion of this final project are the critical resource to keep competitive in this business is trust, company should maintain their strengths, keep the consistency, minimize mistake/error, and To control the financial ratio, company should invest their cash to mutual fund, deposito, buy a fixed asset, etc.Keywords : IE matrix, appraisal firm, business model canvas